IMPROVEMENT OF RETHROMBOSIS DIAGNOSTICS IN STEACS PATIENTS WITH USE OF TELEMONITORING OF ECG - V. E. Oleynikov; E. A. Shitogarova; A. V. Kulyutsin; S. V. Evstigneev (Российский кардиологический журнал)
Aim. To study diagnostic significance of transient ST elevation, revealing with telemetric ECG monitoring in patients with effective systemic thrombolysis (STL) in acute coronary syndrome with ST elevation (STEACS).Material and methods. Totally 56 patients included of both genders, with STEACS, having ECG signs of successful STL during 3 hours after disease had started. All patients in acute coronary unit envirnonment underwent telemetric ECG registration with "Astrocard-Telemetry" complex (CJSC Meditek, Russia) with analysis of ST dynamics by 12-lead automatic regimen with following physician verification. Results. At most the re-elevation of ST was unsymptomatic. By coronary arteriography most patients with registered transient re-elevation episodes had shown thrombosis of infarction-relevant artery.Conclusion. Transient re-elevation of ST by 1 mm and more is an accurate diagnostic criteria of coronary rethrombosis development and makes it possible to identify patients group whom urgent PCI after STL is recommended. Asymptomatic re-elevation episodes of ST can be found on time only with telemetric ECG- monitoring.